2006
DOI: 10.1095/biolreprod.105.050252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Pituitary-Specific Chicken Gonadotropin-Releasing Hormone Receptor and Its Splice Variants1

Abstract: In all vertebrates, GnRH regulates gonadotropin secretion through binding to a specific receptor on the surface of pituitary gonadotropes. At least two forms of GnRH exist within a single species, and several corresponding GnRH receptors (GNRHRs) have been isolated with one form being pituitary specific. In chickens, only one type of widely expressed GNRHR has previously been identified. The objectives of this study were to isolate a chicken pituitary-specific GNRHR and to determine its expression pattern duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
(55 reference statements)
2
25
1
Order By: Relevance
“…It was suggested that GPR147 gene expression is down regulated in response to a surge in circulating estradiol and progesterone levels as the chicken undergoes sexual maturation to allow gonadotropin secretion (Maddineni et al, 2008a). Shimizu and Bédécarrats (2010) showed that GPR147 mRNA level fluctuates in an opposite manner to GnRH-R-III, a pituitary specific form of GnRH receptor, mRNA level in the chicken pituitary (Joseph et al, 2009, Shimizu andBédécarrats, 2006). Higher and lower levels of GPR147 and GnRH-R-III mRNA levels are observed during inactive and active reproductive stages, respectively.…”
Section: Regulation Of Reproductive Development and Maintenancementioning
confidence: 99%
“…It was suggested that GPR147 gene expression is down regulated in response to a surge in circulating estradiol and progesterone levels as the chicken undergoes sexual maturation to allow gonadotropin secretion (Maddineni et al, 2008a). Shimizu and Bédécarrats (2010) showed that GPR147 mRNA level fluctuates in an opposite manner to GnRH-R-III, a pituitary specific form of GnRH receptor, mRNA level in the chicken pituitary (Joseph et al, 2009, Shimizu andBédécarrats, 2006). Higher and lower levels of GPR147 and GnRH-R-III mRNA levels are observed during inactive and active reproductive stages, respectively.…”
Section: Regulation Of Reproductive Development and Maintenancementioning
confidence: 99%
“…Shimizu and Bédécarrats (45) showed that GPR147 mRNA levels fluctuate in an opposite manner to GnRH-receptor-III, a pituitary specific form of GnRH receptor (GnRH-R), in the chicken (46, 47) according to reproductive stages. They demonstrated that the chicken GPR147 inhibits cAMP production, most likely by coupling to G αi .…”
Section: Gnih Receptor and Cell Signalingmentioning
confidence: 99%
“…A novel isoform of cGnRH-R was subsequently cloned by ourselves and others (Joseph et al . 2006, Shimizu & Bedecarrats 2006; Genbank AY895154). The white Leghorn isoform of the novel receptor was designated cGNRHR2 (Shimizu & Bedecarrats 2006), but it can be classified as a type III GnRH receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The white Leghorn isoform of the novel receptor was designated cGNRHR2 (Shimizu & Bedecarrats 2006), but it can be classified as a type III GnRH receptor. Using PCR, this receptor showed expression of two pituitary-specific transcripts (1260 bp full length and 1065 bp splice variant; Shimizu & Bedecarrats 2006), in addition to another 501 bp splice variant that is expressed in different brain regions (Shimizu & Bedecarrats 2006). Inositol phosphate accumulation in response to GnRH-II stimulation was more potent at cGNRHR2 (Shimizu & Bedecarrats 2006) than the response to cGnRH-I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation